Spiritual Capital Innovative Work Behavior and Subjective Well Being of Startup Founders - Agustina, Tri Siwi; GENÇ, Abdullah Talha; Prasetyo, Ari (Pandawan, 2026)
The rapid growth of the startup ecosystem in Indonesia presents substantial opportunities as well as significant challenges for startup founders, particularly in maintaining their subjective well-being. This study aims to examine the effect of spiritual capital on the subjective well-being of startup founders in Surabaya, Indonesia, with innovative work behavior as a mediating variable. This study adopts a quantitative research design using survey data collected from 107 startup founders through a structured questionnaire. The sampling technique employed was convenience sampling. This study employs a reflective measurement model for all latent constructs within the PLS-SEM framework. The findings reveal that spiritual capital has a positive and significant effect on the subjective well-being of startup founders. Furthermore, innovative work behavior partially mediates the relationship between spiritual capital and subjective well-being. These results indicate that spiritual capital not only directly enhances subjective well-being but also indirectly contributes through the promotion of innovative behaviors among startup founders.